Exploring Genius Loci Changes in Panembahan Yogyakarta: From Residential to Cafe Function - Vanti, Chairunisa Dwitya; Zakiyah, Zahra; Agustiananda, Putu Ayu Pramanasari; Sinaga, Bryan Putra Parsada (Journal of Architectural Design and Urbanism, 2024)
This research paper aims to investigate the concept of "genius loci" in Yogyakarta, specifically in the Panembahan area of Baluwarti. With a particular focus on how the unique character of this settlement is shaped by its physical environment, historical heritage and the collective consciousness of its residents. Through an examination of tangible and intangible elements such as traditional javaneese houses (Joglo) and large white fort, embodies the historical and cultural identity of the region. This research also examines how modern economic demands have led residents to convert their homes into commercial establishments. The research employees direct observation, interviews, and literature review to assess changes in the aspects of image, space and character. The findings indicate that while some buildings retain traditional essence, others undergone significant modification, leading to potential erosion of the local cultural identity. The study aims to provide guidelines for preserving the genius loci in the face of modernization, ensuring sustainable cultural heritage.